Use of neem and neem based products in organic farming - Gupta, Arbind Kumar (Indian Farming, 2022)
Neem products are eco-friendly and superior in quality compared to chemical pesticides. By using these products, we can overcome the ecological and health threats imposed by chemical pesticides. Neem based products like neem cakes are a boon for organic agriculture in order to maintain sustainability of environment.